Evaluation Of Anticonvulsant Activity Of Magnesium Oxide Alone And With Phenytoin Against Experimentally Induced Convulsions In Albino Rats - DR.RAGHU PRASADA M.S; DR NARENDRANATH S; DR. H.S. SOMASHEKAR; DR.SHANKAR A.S; DR. PRASHANTH.P (International Journal of Pharma and Bio Sciences, 2012)
The objective of the study was to find the effect of oral magnesium oxide supplementation alone and with standard anticonvulsive doses of phenytoin in the animal models of maximal electroshock seizures (MES) induced seizures. Healthy male albino rats (n=42) were divided into 6 groups, each group including seven animals. Magnesium oxide (Mgo ) supplementation is given orally in the dose ( 500 mg/kg/day) for 10 days for all groups except for group A(control) . On day 10, responses to MES (180 mA for 0.2 s) were tested 1hr after pre-administration of phenytoin orally in different doses(100,200,400 mg/kg ). In Combination studies in group B,C and D the time taken for recovery was better in low dose magnesium and phenytoin combination (group B) . Compared to magnesium alone group (group F) all the combination groups (group B,C and D) were better in controlling THLE (Tonic Hind Limb Extension).Study also shows that Magnesium may help in faster recovery from seizure activity. Hence, we may reduce the standard dose of each drug and related adverse effects.